2018
DOI: 10.1016/j.bpj.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Statistical Multiplicity of Infection on Virus Quantification and Infectivity Assays

Abstract: Many biological assays are employed in virology to quantify parameters of interest. Two such classes of assays, virus quantification assays (VQAs) and infectivity assays (IAs), aim to estimate the number of viruses present in a solution and the ability of a viral strain to successfully infect a host cell, respectively. VQAs operate at extremely dilute concentrations, and results can be subject to stochastic variability in virus-cell interactions. At the other extreme, high viral-particle concentrations are use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Note that this expression is largely equivalent to that obtained by Mistry et al [8] in the context of estimating the TCID 50 of a virus sample, and by many others in the broader context of infection dose quantification [12,13].…”
Section: Pðpjdataþ ¼supporting
confidence: 62%
See 2 more Smart Citations
“…Note that this expression is largely equivalent to that obtained by Mistry et al [8] in the context of estimating the TCID 50 of a virus sample, and by many others in the broader context of infection dose quantification [12,13].…”
Section: Pðpjdataþ ¼supporting
confidence: 62%
“…., D 11 ¼ 10 À 7 ), and the total volume of inoculum (diluted virus sample + dilutant) placed in each well is V inoc = 0.1 mL. Now, consider that a virus sample is measured using this ED experiment and one observes (8,8,8,8,8,7,7,5,2,0,0) infected wells out of 8 replicates at each of the 11 dilutions, as illustrated in Fig 1A.…”
Section: Key Features Of Midsin's Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that within this initial group were individual transcription factors, or combinations thereof, able to reprogram MEFs to a hair cell-like state. The low level of reprogramming efficiency is expected when large numbers of factors are infected simultaneously, since only a subset of factors is expected to infect any given cell ( Phan and Wodarz, 2015 ; Mistry et al, 2018 ), and since using large numbers of factors, and/or virus, is likely to challenge cellular transcription/translational machinery, thus further reducing efficiency ( Babos et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…This makes it problematic to experimentally achieve the desired multiplicity of infection when inoculating from a sample quantified via the SK or RM methods. Many have proposed replacements for the RM and SK calculations with some based on logit or probit transforms of the data [2,4,6] and others on statistical analysis of the ED assay output [6,7]. Sadly, none of these improvements were widely adopted, possibly due to a lack of visibility of these publications, or the lack of widespread awareness of the limitations of the RM and SK methods.…”
Section: Introductionmentioning
confidence: 99%